INVESTMENT ACTIVITY OF SMALL COMMUNES IN EASTERN POLAND – RYKI COMMUNE CASE STUDY - Wróblewska, Emilia (Acta Scientiarum Polonorum. Oeconomia, 2010)
Investment activity is an important factor for local development in Poland. The paper’s subject concentrates on conditions of such activity in the years 2004–2008 in Ryki commune, located in the North-West part of Lubelskie voivodeship. It stems from the analysis contained in the paper that the community has low investment expenditure per capita, as compared to the poviat, the voivodeship and the average for Poland. Among realized investments in the analyzed period, investments of sections: „Transport & Communications” and „Education & Upbringing” had the largest share. Moreover, the main source of funds was the budget supported by credits and loans. Use of EU funds in the Ryki community was not significant. The analysis allows to make the conclusion that the scope of investments was typical for small communes and for the region.